Women's narratives about alcohol use during pregnancy: a narrative-discursive study - Matebese, Sibongile (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
While research has explored the risk factors that contribute to alcohol use during pregnancy among South African women, such studies have mostly been quantitative in nature. There is a growing body of research that contextualises and articulates the attitudes, beliefs, and underlying motivations that influence drinking during pregnancy. However, few qualitative studies explore the cultural, economic, familial, and social contexts within which drinking during pregnancy takes place. Studies which have explored these contexts have been conducted in other geographical regions such as Australia, Canada, New Zealand, and the United States but their findings are not generalisable to South Africa. Drawing on a feminist poststructuralist as well as a narrative-discursive approach including Foucault's (1978) theory of power, this study sought to explore women's narratives of the personal and interpersonal circumstances under which drinking during pregnancy takes place in terms of the discourses used to construct these narratives and the subject positions made available within these discourses. This allowed for the practice of alcohol use during pregnancy to be understood within the social and cultural narratives, practices, and discourses around pregnancy as well as gendered and social relations. Using the narrative interview method set out by Wengraf (2001), thirteen, unemployed 'Black' women from an area in the Eastern Cape were recruited and interviewed. Seven discourses emerged from the narratives namely, a discourse of 'stress and coping' 'hegemonic masculinities', 'peer pressure', 'disablement and developmental delay', 'good mothering/appropriate pregnancies', 'culture', and 'religion'. These discourses informed the five narrative categories which emerged: narratives about the pregnancy, narratives about the drinking, narratives that justify/explain drinking, narratives that condemn the drinking, and narratives about the women knowing the effects of drinking during pregnancy. Within these narratives, the women mainly positioned themselves as dependent on alcohol during their pregnancies in order to cope with stress caused by various circumstances which were mainly centred on a lack of support from their partners, paternity denial, infidelity and unreliableness. As such, the women in this study mainly justified their drinking during pregnancy and in constructing this narrative, the 'stress and coping' discourse as well as the 'male/masculine provider' discourse were mainly drawn upon. In reflecting on this analysis, this study argues that alcohol use during pregnancy should be understood within the broader environmental and social context that makes a pregnancy challenging and/or difficult and thus necessitates drinking during pregnancy. Recommendations for future research include expanding the diversity of participants as well as interviewing healthcare providers and women who are currently pregnant, drinking, and part of an intervention aimed at addressing alcohol use during pregnancy so as to obtain a holistic understanding of engaging in this practice. The study makes key recommendations for interventions in practice to help work towards ensuring that the practice of alcohol use during pregnancy is not individualised, decontextualized, and stigmatised.
Keywords: Pregnant women -- South Africa -- Social conditions; Pregnant women -- South Africa -- Alcohol use; Pregnant women -- South Africa -- Psychology